SOME ISSUES OF THE PROCEDURAL PECULIARITIES OF REVIEWING CIVIL CASES ON LABOR DISPUTES IN COURTS OF APPEAL - А.Z. Issayeva,; B.Zh. Aitimov, (Academic Journal of Physical and Chemical Sciences, 2019)
A review of labor disputesby the appeals instanceof court rulings may results in their cancellation if there are grounds. Investigating a number of civil cases, the authors believe that a formal violation of procedural rules should not cause a review of court rulings. Highlighting the classification of the grounds to cancel the court decisions on labor cases, critically evaluating the position of the Supreme Court of the Republic of Kazakhstan regarding the value of the correct distribution of the burden of proof, the authors substantiate the possibility of assessing such procedural violation as conditional. The authors believe that the court’s disregard for the significance of evidentiary presumptions will lead to wrong decision.